Highly Efficient Hybrid Polymer and Amorphous Silicon Multijunction Solar Cells with Effective Optical Management. Issue 11 (18th January 2016) - Tan, Hairen; Furlan, Alice; Li, Weiwei; Arapov, Kirill; Santbergen, Rudi; Wienk, Martijn M.; Zeman, Miro; Smets, Arno H. M.; Janssen, René A. J.
Abstract : Highly efficient hybrid multijunction solar cells are constructed with a wide‐bandgap amorphous silicon for the front subcell and a low‐bandgap polymer for the back subcell. Power conversion efficiencies of 11.6% and 13.2% are achieved in tandem and triple‐junction configurations, respectively. The high efficiencies are enabled by deploying effective optical management and by using photoactive materials with complementary absorption.